Shared decision making in contraceptive counseling - Dehlendorf, Christine; Grumbach, Kevin; Schmittdiel, Julie A.; Steinauer, Jody (Contraception (Stoneham), 2017)
Shared decision making (SDM) is a potentially valuable but underexplored approach to contraceptive counseling. We determined the correlation between patient report of SDM and of whether their provider had a method preference with measures of satisfaction. Women reporting SDM were more likely to be satisfied with counseling than those reporting a provider-driven decision and were more likely to be satisfied with their method than those reporting a patient-driven decision. Patients who felt that the provider had a method preference were less likely to be satisfied with their method. SDM in contraceptive counseling is associated with patient satisfaction.